Articulating biological and cultural evolution Comment on “Surname distribution in population genetics and in statistical physics” by Paolo Rossi - Zanette, Damian Horacio (2013)
Fil: Zanette, Damian Horacio. Comisión Nacional de Energía Atómica. Gerencia del Area de Investigación y Aplicaciones No Nucleares. Gerencia de Física (centro Atómico Bariloche); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina